2005
DOI: 10.1105/tpc.104.028522
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoserines on Maize CENTROMERIC HISTONE H3 and Histone H3 Demarcate the Centromere and Pericentromere during Chromosome Segregation

Abstract: We have identified and characterized a 17-to 18-kD Ser50-phosphorylated form of maize (Zea mays) CENTROMERIC HISTONE H3 (phCENH3-Ser50). Immunostaining in both mitosis and meiosis indicates that CENH3-Ser50 phosphorylation begins in prophase/diplotene, increases to a maximum at prometaphase-metaphase, and drops during anaphase. Dephosphorylation is precipitous (approximately sixfold) at the metaphase-anaphase transition, suggesting a role in the spindle checkpoint. Although phCENH3-Ser50 lies within a region t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 57 publications
1
50
0
2
Order By: Relevance
“…All cells were stained with 0.01 mg/ml DAPI (4,6-diamidino-2-phenylindole) for 10 min, mounted in Mowiol mounting medium (Harlow and Lane 1988), and sealed with nail polish. Protein blot analysis: Maize protein was extracted from young ears $10 cm in length (Zhang et al 2005) and from cultured mouse neocortical neuron cells (Dravid et al 2005). Protein extraction and protein blot analysis were carried out as previously described (Zhang et al 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All cells were stained with 0.01 mg/ml DAPI (4,6-diamidino-2-phenylindole) for 10 min, mounted in Mowiol mounting medium (Harlow and Lane 1988), and sealed with nail polish. Protein blot analysis: Maize protein was extracted from young ears $10 cm in length (Zhang et al 2005) and from cultured mouse neocortical neuron cells (Dravid et al 2005). Protein extraction and protein blot analysis were carried out as previously described (Zhang et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Protein blot analysis: Maize protein was extracted from young ears $10 cm in length (Zhang et al 2005) and from cultured mouse neocortical neuron cells (Dravid et al 2005). Protein extraction and protein blot analysis were carried out as previously described (Zhang et al 2005). A single nitrocellulose membrane was cut into four pieces and incubated with different primary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, little is known about PTMs on CenH3. A role for phosphorylation of human CENP-A by Aurora B kinase has been described in the final stages of cytokinesis (20), and maize CenH3 is also phosphorylated (21). Additionally, Cse4 levels in the cell are controlled by ubiquitination of Cse4 that is mediated by the ubiquitin ligase Psh1.…”
mentioning
confidence: 99%
“…By contrast, there is a uniform distribution along the meiotic chromosomes at metaphase I. Recently, phosphoserines on the specific centromeric histone H3 versus the canonical histone H3 were reported to delineate the centromeric and pericentromeric regions of the chromosome with regard to the functions of chromosome segregation and cohesion (Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Kaszas and Cande (2000) found that phosphorylation of histone H3 Ser-10 was correlated with the maintenance of sister chromatid cohesion. Phosphorylation of H3 is typically detected in pericentromeric regions of the mitotic chromosome and in meiosis (Zhang et al, 2005). In the afd1 mutant, phosphorylation is found only at pericentromeric regions in metaphase I.…”
Section: Introductionmentioning
confidence: 99%